ChemInform Abstract: GeAs: Highly Anisotropic van der Waals Thermoelectric Material. Issue 28 (June 2016) - Lee, Kathleen; Kamali, Saeed; Ericsson, Tore; Bellard, Maverick; Kovnir, Kirill
Abstract: GeAs and Sn‐doped GeAs are prepared from the elements (1373 K, 4—5 d) and characterized by powder XRD, SEM, 119 Sn Moessbauer spectroscopy, transport measurements, and TB‐LMTO‐ASA calculations.